Implementation of the Markowitz Model in Efficient Portfolio Construction: Analysis of the Investor33 Index After the Major Evaluation of 2025 - Kharismawan, Bagus; Andriani, Prima (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to create an optimal portfolio of stocks included in the Investor33 index, an index created and managed by the Indonesia Stock Exchange in collaboration with the media company PT Media Investor Indonesia, using the Markowitz model approach. The portfolio optimization aims to provide an alternative for rational investment decision-making based on a balance between stock returns and risk. The data used for portfolio construction is monthly return data from May 2022 to May 2025 for 33 stocks in the Investor33 index, which were evaluated by the Indonesia Stock Exchange in May 2025 and effective from June 2 to November 28, 2025. Based on the calculations, nine stocks form the optimal portfolio: BNGA, INDF, ICBP, PGAS, AKRA, BRIS, ANTM, AMRT and MYOR. This portfolio provides an estimated return of 1.316% per month with a risk level (variance) of 0.151%. These results indicate that the mean-variance approach in the Markowitz Model remains relevant for forming efficient portfolios for the leading stock groups in the Indonesian capital market.